Irbesartan in Hypertensive Non Diabetic Advanced Chronic Kidney Disease: Comparative Study With Losartan (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Antihypertensive, Reno protective,antiproteinuric and cardioprotective effect of AngiotensinReceptor Blocker (ARB) is well proved in diabetic andnondiabetic nephropathy but not free of side effect inAdvanced Chronic Kidney Disease (ACKD) patients.Most studies with ARB done on diabetic patients andsome showed controversial result. Our aim is to comparethe effects of two ARB (Losartan and Irbesartan) onhypertensive, nondiabetic ACKD patients. Materials and methods: Nondiabetic patients with ACKD (CrCl< 30 ml/min) attended in medicine and Nephrology Department of Chittagong Medical College Hospital (CMCH) from March 2013 to May 2014 wereenrolled in a prospective longitudinal study with 1:1randomization.Results: Among them 14 were male and 16 were female.Most patients were house wife, primary educated andnonsmoker. Chronic Kidney Disease (CKD) of 17 patientswas due to Glomerulonephritis (GN) and in rest 13 wasdue to hypertension (HTN). Ingroup A: 15 patientsreceived Losartan once daily with dose 50-100 mg/day. Ingroup B: 15 patients received Irbesartan mono dose 150300mg/day. We studied Systolic Blood Pressure (SBP),Diastolic Blood Pressure (DBP), Pulse Blood Pressure(PBP), renal function (CrCl), Proteinuria, Serum K andserum uric acid at month 0, 3, 6, 9 and 12. At 12 monthscomparing group A and group B we found SBP decreased20.93% Vs 19.85%, DBP decreased 12.84% Vs 15.03%,PBP decreased 30.05% vs 25.73%, CrCl reduced 6.99%+Vs 10.81%. Proteinuria diminished 14.30% Vs 19.09%,serum K+ increased 26.58% Vs 12.07% (Statisticallysignificant, p = 0.016) and Uric acid decreased 30.65% Vs5.37% (Statistically significant, p